Metallosilicate catalyst regeneration

JP7668789B2Active Publication Date: 2025-04-25DOW GLOBAL TECHNOLOGIES LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022515103
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-29
Publication Date
2025-04-25
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

The existing metallosilicate catalysts used in the production of second-class alcohol ethoxylate surfactants suffer from rapid fouling, leading to a short service life, high energy costs, and low monoalkyl ether selectivity due to conventional regeneration processes at temperatures above 450°C, which are inefficient and costly.

Method used

A regeneration process for metallosilicate catalysts is developed that operates at temperatures below 450°C, using inert atmospheres or vacuum, achieving a recycled catalyst with over 80% monoalkyl ether selectivity and maintaining catalyst activity.

Benefits of technology

This process reduces energy costs and increases monoalkyl ether production speed while maintaining high selectivity, offering a more efficient and cost-effective catalyst regeneration method.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to at least one feature of the present disclosure, the method includes the steps of: (a) providing a metallosilicate catalyst that has been used to catalyze a chemical reaction; and (b) heating the metallosilicate catalyst to a temperature of 200°C to 425°C for a time period of 0.5 hours to 5 hours.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Technical field This disclosure relates, in general terms, to metallosilicate catalysts, and more specifically, to the regeneration of metallosilicate catalysts.

[0002] Introduction The production of secondary alcohol ethoxylate surfactants can be carried out by catalytic ethoxylation of (poly)alkylene glycol monoalkyl ethers ("monoalkyl ethers"). Monoalkyl ethers are formed from olefins and (poly)alkylene glycols using a crystalline metallosilicate catalyst ("metallosilicate catalyst"). The metallosilicate catalyst provides selectivity for monoalkyl ethers of over 80% with an olefin conversion rate of over 5%, which is advantageous because (poly)alkylene glycol dialkyl ethers ("dialkyl ethers") are detrimental to the properties of secondary alcohol ethoxylate surfactants.

[0003] While offering over 80% selectivity for monoalkyl ethers, metallosilicate catalysts foul quickly, resulting in short service life, low monoalkyl ether production rates, and the need to repeat the metallosilicate catalyst regeneration process. Regeneration of metallosilicate catalysts is performed at high temperatures for extended periods to remove fouling agents. For example, U.S. Patent No. 6,417,408 explains that catalyst regeneration is preferable to be performed by calcining the catalyst at temperatures above 450°C, as temperatures below 450°C leave a very large amount of residual carbon (as evident by the visual residue of residual carbon), and as a result, the catalyst is thought to exhibit a shorter regeneration period and lower monoalkyl ether production. The repetitions essential to conventional regeneration processes are costly and require specialized equipment.

[0004] Therefore, it is remarkable to discover a metallosilicate catalyst regeneration process that runs at temperatures below 450°C and yields a catalyst with a monoalkyl ether production rate and monoalkyl ether selectivity exceeding 80%, comparable to that of an unused regenerated catalyst. [Overview of the project]

[0005] The present invention provides a solution for providing a catalyst regeneration process that is performed at temperatures below 450°C and yields a catalyst having a monoalkyl ether production rate equivalent to that of an unused regenerated catalyst and a monoalkyl ether selectivity of more than 80%.

[0006] This invention is the result of the unexpected discovery that regenerating a fouled metallosilicate catalyst at temperatures of 200°C to 425°C provides a regenerated catalyst with monoalkyl ether production rates equivalent to and / or even better than those of an unused regenerated catalyst, as well as monoalkyl ether selectivity exceeding 80% at an olefin conversion rate of 5% or more. Such results are remarkable in that regeneration temperatures 100°C and below the acceptable minimum limit established by the prior art can provide superior monoalkyl ether production rates and selectivity values ​​compared to conventional processes at higher temperatures. Even more remarkable is that while conventional regeneration processes rely on the oxidation of fouling, this invention can utilize an inert atmosphere or even a vacuum and still achieve superior results compared to conventional processes. Thus, not only can energy cost savings be achieved through this remarkably low-temperature regeneration process, but superior production rates and monoalkyl ether selectivity can also be achieved through the use of this invention.

[0007] According to at least one feature of the present disclosure, the method comprises (a) providing a metalrosilicate catalyst that has been used to catalyze a chemical reaction, and (b) heating the metalrosilicate catalyst to a temperature of 200°C to 425°C for a period of 0.5 hours to 5 hours. [Modes for carrying out the invention]

[0008] As used herein, the term "and / or" means, when used in the enumeration of two or more items, that any one of the enumerated items may be used on its own, or any combination of two or more of the enumerated items may be used. For example, if a composition is described as containing components A, B, and / or C, the composition may contain A alone, B alone, C alone, a combination of A and B, a combination of A and C, a combination of B and C, or a combination of A, B, and C.

[0009] Unless otherwise specified, all scopes include endpoints.

[0010] Unless the date is indicated by a hyphenated two-digit number in the test method number, the test method refers to the most recent test method as of the priority date of this document. References to test methods include both references to testing societies and test method numbers. Organizations of test methods are referred to by one of the following abbreviations: ASTM refers to ASTM International (formerly the American Society for Testing and Materials), EN refers to European standards, DIN refers to the Deutsches Institut für Normung, and ISO refers to the International Organization for Standardization.

[0011] Unless otherwise specified, the IUPAC code describing the crystal structures precisely as defined by the Structural Committee of the International Zeolite Association refers to the most recent designation as of the priority date of this document.

[0012] As used herein, the term weight percent ("weight %) indicates that an ingredient is a weight percent of the total weight of the composition shown.

[0013] method The method of the present invention is directed to the regeneration of a metallosilicate catalyst. The method may include providing a metallosilicate catalyst that has been used to catalyze a chemical reaction, and heating the metallosilicate catalyst to a temperature of 200°C to 425°C for a period of 0.5 hours to 5 hours. The method may further include catalyzing a chemical reaction between an olefin and an alcohol using the metallosilicate catalyst, and producing an alkylene glycol monoalkyl ether.

[0014] Olefin The olefin used in the method can be linear, branched, acyclic, cyclic, or a mixture thereof. The olefin can have from 5 to 30 carbons (i.e., C5 - C 30 ). The olefin can have 5 or more carbons, or 6 or more carbons, or 7 or more carbons, or 8 or more carbons, or 9 or more carbons, or 10 or more carbons, or 11 or more carbons, or 12 or more carbons, or 13 or more carbons, or 14 or more carbons, or 15 or more carbons, or 16 or more carbons, or 17 or more carbons, or 18 or more carbons, or 19 or more carbons, or 20 or more carbons, or 21 or more carbons, or 22 or more carbons, or 23 or more carbons, or 24 or more carbons, or 25 or more carbons, or 26 or more carbons, or 27 or more carbons, or 28 or more carbons, or 29 or more carbons, while at the same time having 30 or fewer carbons, or 29 or fewer carbons, or 28 or fewer carbons, or 27 or fewer carbons, or 26 or fewer carbons, or 25 or fewer carbons, or 24 or fewer carbons, or 23 or fewer carbons, or 22 or fewer carbons, or 21 or fewer carbons, or 20 or fewer carbons, or 19 or fewer carbons, or 18 or fewer carbons, or 17 or fewer carbons, or 16 or fewer carbons, or 15 or fewer carbons, or 14 or fewer carbons, or 13 or fewer carbons, or 12 or fewer carbons, or 11 or fewer carbons, or 10 or fewer carbons, or 9 or fewer carbons, or 8 or fewer carbons, or 7 or fewer carbons, or 6 or fewer carbons.

[0015] Olefins can include alkenes such as alpha (α) olefins, internal disubstituted olefins, or cyclic structures (e.g., C3 - C 12 cycloalkenes). An α olefin contains an unsaturated bond at the α position of the olefin. Suitable α olefins can be selected from the group consisting of propylene, 1 - butene, 1 - hexene, 4 - methyl - 1 - pentene, 1 - heptene, 1 - octene, 1 - decene, 1 - dodecene, 1 - tetradecene, 1 - hexadecene, 1 - octadecene, 1 - eicosene, 1 - docosene, and combinations thereof. An internal disubstituted olefin contains an unsaturated bond not at the terminal positions on the olefin. Internal olefins can be selected from the group consisting of 2 - butene, 2 - pentene, 2 - hexene, 3 - hexene, 2 - heptene, 3 - heptene, 2 - octene, 3 - octene, 4 - octene, 2 - nonene, 3 - nonene, 4 - nonene, 2 - decene, 3 - decene, 4 - decene, 5 - decene, and combinations thereof. Other exemplary olefins can include butadiene and styrene.

[0016] Examples of suitable commercially available olefins include NEODENE™ 6 - XHP, NEODENE™ 8, NEODENE™ 10, NEODENE™ 12, NEODENE™ 14, NEODENE™ 16, NEODENE™ 1214, NEODENE™ 1416, NEODENE™ 16148, manufactured by Shell, The Hague, Netherlands.

[0017] Alcohol The alcohol used in this method may contain a single hydroxyl group, two hydroxyl groups (i.e., glycols), or three hydroxyl groups. The alcohol may contain one or more carbon atoms, or two or more carbon atoms, or three or more carbon atoms, or four or more carbon atoms, or five or more carbon atoms, or six or more carbon atoms, or seven or more carbon atoms, or eight or more carbon atoms, or nine or more carbon atoms, while simultaneously containing 10 or fewer carbon atoms, or nine or fewer carbon atoms, or eight or fewer carbon atoms, or seven or fewer carbon atoms, or six or fewer carbon atoms, or five or fewer carbon atoms, or four or fewer carbon atoms, or three or fewer carbon atoms, or two or fewer carbon atoms. The alcohol may be selected from the group consisting of methanol, ethanol, monoethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, polyethylene glycol, monopropylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,3-propanediol, 1,2-butanediol, 2,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,4-cyclohexanemethanediol, glycerol, and / or combinations thereof. According to various examples, the alcohol is (poly)alkylene glycol such as monoethylene glycol, diethylene glycol, propylene glycol, and triethylene glycol.

[0018] The molar ratio of alcohol to olefin in this method may be 20:1 or less, or 15:1 or less, or 10:1 or less, or 9:1 or less, or 8:1 or less, or 7:1 or less, or 6:1 or less, or 5:1 or less, or 4:1 or less, or 3:1 or less, or 2:1 or less, or 0.2:1 or less, while simultaneously being 0.1:1 or more, or 1:1 or more, or 1:2 or more, or 1:3 or more, or 1:4 or more, or 1:5 or more, or 1:6 or more, or 1:7 or more, or 1:8 or more, or 1:9 or more, or 1:10 or more, or 1:15 or more, or 1:20 or more.

[0019] Metallosilicate catalyst As used herein, the term "metallosilicate catalyst" refers to an aluminosilicate (commonly referred to as zeolite) compound having a crystal lattice in which one or more metal elements are substituted within the crystal lattice instead of silicon atoms. The crystal lattice of the metallosilicate catalyst forms cavities and channels inside, where cations, water, and / or small molecules can be present. The alternative metal element can include one or more metals selected from the group consisting of B, Al, Ga, In, Ge, Sn, P, As, Sb, Sc, Y, La, Ti, Zr, V, Cr, Mn, Pb, Pd, Pt, Au, Fe, Co, Ni, Cu, Zn. The metallosilicate catalyst may not substantially contain Hf. According to various examples, the metallosilicate may have a silica-to-alumina ratio of 5:1 to 1,500:1 when measured using neutron activation analysis. The silica-to-alumina ratio can be 5:1 to 1,500:1, or 10:1 to 500:1, or 10:1 to 400:1, or 10:1 to 300:1, or 10:1 to 200:1. Such a silica-to-alumina ratio can be advantageous for providing a highly homogeneous metallosilicate catalyst having an organophilic-hydrophobic selectivity for adsorbing nonpolar organic molecules.

[0020] The metallosilicate catalyst may have one or more ion-exchangeable cations outside the crystal lattice. The ion-exchangeable cations are H + , Li + , Na + , Rb + , Cs + , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Sc 3+ , Y 3+ , La 3+ , R4N + , R4P + (where R is H or alkyl) may be included.

[0021] Metallosilicate catalysts can adopt a variety of crystal structures. Specific examples of metallosilicate catalyst structures include MFI (e.g., ZSM-5), MEL (e.g., ZSM-11), BEA (e.g., β-type zeolite), FAU (e.g., Y-type zeolite), MOR (e.g., mordenite), MTW (e.g., ZSM-12), and LTL (e.g., Linde L), as described using the IUPAC code according to the terminology system of the Structural Committee of the International Zeolite Association.

[0022] The crystalline framework of metallosilicate catalysts is represented by a network of molecular-sized channels and cages consisting of corner-shared tetrahedron [TO4](T=Si or Al) primary building blocks. Negative charges can be introduced onto the framework by isomorphic substitution of tetravalent silicon atoms with trivalent metal (e.g., aluminum) atoms. Overall charge neutrality is then achieved by introducing cationic species that compensate for the resulting negative lattice charge. When such charge compensation is provided by protons, a Brønsted acid moiety is formed, making the H-type of the resulting zeolite a potent solid Brønsted acid.

[0023] Metallosilicate catalysts can be used in various forms in this method. For example, the metallosilicate catalyst may be a powder (e.g., particles with a longest length dimension of less than 100 micrometers), granular (e.g., particles with a longest length dimension of 100 micrometers or more), or a molded article of powder and / or granular metallosilicate catalyst.

[0024] The metallosilicate catalyst is 100m 2 / g or more, or 200m 2 / g or more, or 300m 2 / g or more, or 400m 2 / g or more, or 500m 2 / g or more, 600m 2 / g or more, or 700m 2 / g or more, or 800m 2 / g or more, or 900m2 / g or more, while simultaneously, 1000m 2 / g or less, or 900m 2 / g or less, or 800m 2 / g or less, or 700m 2 / g or less, or 600m 2 / g or less, or 500m 2 / g or less, or 400m 2 / g or less, or 300m 2 / g or less, or 200m 2 It may have a surface area of ​​less than / g. The surface area is measured according to ASTM D4365-19.

[0025] Metallosilicate catalysts can be synthesized by hydrothermal synthesis. For example, a metallosilicate catalyst can be synthesized by heating a composition containing a silica source (e.g., silica sol, silica gel, and alkoxysilane), a metal source (e.g., metal sulfates, metal oxides, metal halides, etc.), and a quaternary ammonium salt such as tetraethylammonium salt or tetrapropylammonium salt to a temperature of about 100°C to about 175°C until a crystalline solid is formed. The resulting crystalline solid is then filtered, washed with water, dried, and calcined at a temperature of 350°C to 600°C.

[0026] Suitable commercially available metallosilicate catalysts include CP814E, CP814C, CP811C-300, CBV 712, CBV 720, CBV 760, CBV 2314, and CBV 10A, all manufactured by ZEOLYST INTERNATIONAL in Conshohocken, PA.

[0027] Formation of monoalkyl ethers Using a metallosilicate catalyst to catalyze the chemical reaction between olefins and alcohols yields alkylene glycol monoalkyl ethers. A solvent is used to facilitate the chemical reaction. The chemical reaction between olefins and alcohols is catalyzed by the metallosilicate catalyst in the reactor to produce monoalkyl ethers. Various monoalkyl ethers can be produced for different applications by changing which olefin and / or which alcohol is used. Monoalkyl ethers are utilized for many applications, such as solvents, surfactants, and chemical intermediates.

[0028] The reaction between olefins and alcohols can occur at temperatures between 50°C and 300°C, or between 100°C and 200°C. In specific examples, the reaction can be carried out at 150°C. The reaction between olefins and alcohols can be carried out in batch reactors, continuous stirred-tank reactors, continuous fixed-bed reactors, or fluidized-bed reactors. In the operation of the chemical reaction, the Brønsted acid moiety of the metallosilicate catalyst can catalyze the etherification of olefins to alcohols through an addition reaction. The reaction between olefins and alcohols produces monoalkyl ethers.

[0029] The addition reaction of olefins to glycols can form not only monoalkyl ethers but also dialkyl ethers. Metallosilicate catalysts may exhibit selectivity to produce alkylene monoalkyl ethers but not dialkyl ethers. The selectivity for monoalkyl ethers may be 70% or more, or 75% or more, or 80% or more, or 85% or more, or 90% or more, or 95% or more, or 99% or more, while simultaneously being 100% or less, or 95% or less, or 90% or less, or 85% or less, or 80% or less, or 75% or less. The selectivity of dialkyl ethers may be 0% or greater, or 2% or greater, or 4% or greater, or 6% or greater, or 8% or greater, or 10% or greater, or 12% or greater, or 14% or greater, or 16% or greater, or 18% or greater, while simultaneously being 20% ​​or less, or 18% or less, or 16% or less, or 14% or less, or 12% or less, or 10% or less, or 8% or less, or 6% or less, or 4% or less, or 2% or less.

[0030] The yield of the monoalkyl ether is calculated by multiplying the amount of olefin conversion by the selectivity of the monoalkyl ether. The yield of alkylene glycol monoalkyl ether can be 10% or more, or 15% or more, or 20% or more, or 25% or more, or 30% or more, or 35% or more, while simultaneously being 40% or less, or 35% or less, or 30% or less, or 25% or less, or 20% or less, or 15% or less. The yield of the monoalkyl ether is a measure of catalytic activity and selectivity and a good measure of the rate of metallosilicate catalyst formation.

[0031] During the reaction between olefins and alcohols, the catalyst fouls. Fouling has the effect of deactivating the catalyst within a few hours (i.e., losing >50% of its etherification activity).

[0032] Heating of metallosilicate catalysts Regeneration of the metalrosilicate catalyst is carried out by heating the metalrosilicate catalyst to a temperature of 200°C to 450°C for 0.5 to 5 hours. Heating of the metalrosilicate catalyst can be carried out in various ovens, furnaces, and enclosures. For example, regeneration can occur in enclosures such as rotary kilns, box furnaces, fluidized bed furnaces, roller hearth kilns, and tubes equipped with heating elements and mesh belt furnaces. The metalrosilicate catalyst may be removed from the reactor before heating and regeneration, or it may remain in the reactor. Regeneration and heating of the metalrosilicate catalyst can be carried out in the absence of liquid (i.e., the metalrosilicate catalyst is dried before and / or during regeneration). For example, the metalrosilicate catalyst may be removed and dried, or it may be dried in the reactor (e.g., in the case of a fluidized bed furnace).

[0033] The regeneration of metalrosilicate catalysts can be carried out in oxygen in the atmosphere (i.e., calcination), under an atmosphere that is inert to the catalyst and fouls over the metalrosilicate catalyst, or under vacuum. The inert atmosphere may include nitrogen, argon, helium, CO2, other gases inert to fouling, and / or combinations thereof. The inert atmosphere may contain 60 volume percent ("vol%") or more, or 70 volume percent or more, or 80 volume percent or more, or 90 volume percent or more, while simultaneously containing 100 volume percent or less, or 90 volume percent or less, or 80 volume percent or less, or 70 volume percent or less of the inert component. The volume percentage is measured at the regeneration temperature as the percentage of the volume occupied by the inert component divided by the total cavity space in which the metalrosilicate catalyst exists. Such an inert atmosphere can be achieved by passing an inert gas through the metalrosilicate catalyst at a constant rate during heating. The heating of the metallosilicate catalyst may be performed under pressures of 4000 Pa or less, or 3000 Pa or less, or 2000 Pa or less, or 1000 Pa or less, or 900 Pa or less, or 800 Pa or less, or 700 Pa or less, or 600 Pa or less, or 500 Pa or less, or 400 Pa or less, or 300 Pa or less, or 200 Pa or less, or 100 Pa or less, or 50 Pa or less, or 10 Pa or less, or 5 Pa or less.

[0034] The regeneration of the metallosilicate catalyst may be carried out at temperatures above 200°C, or above 225°C, or above 250°C, or above 275°C, or above 300°C, or above 325°C, or above 350°C, or above 375°C, or above 400°C, or above 425°C, while simultaneously at temperatures below 450°C, or below 425°C, or below 400°C, or below 375°C, or below 350°C, or below 325°C, or below 300°C, or below 275°C, or below 250°C, or below 225°C.

[0035] Regeneration of the metallosilicate catalyst is performed for 0.5 hours or more, or 0.75 hours or more, or 1.00 hours or more, or 1.25 hours or more, or 1.50 hours or more, or 1.75 hours or more, or 2.00 hours or more, or 2.25 hours or more, or 2.50 hours or more, or 2.75 hours or more, or 3.00 hours or more, or 3.25 hours or more, or 3.50 hours or more, or 3.75 hours or more, or 4.00 hours or more, or 4.25 hours or more, or 4.50 hours or more, or 4.75 hours or more. On the other hand, it may be executed simultaneously for 5.00 hours or less, or 4.75 hours or less, or 4.50 hours or less, or 4.25 hours or less, or 4.00 hours or less, or 3.75 hours or less, or 3.50 hours or less, or 3.25 hours or less, or 3.00 hours or less, or 2.75 hours or less, or 2.50 hours or less, or 2.25 hours or less, or 2.00 hours or less, or 1.75 hours or less, or 1.50 hours or less, or 1.25 hours or less, or 1.00 hours or less, or 0.75 hours or less.

[0036] advantage The use of the present invention can offer various advantages. Firstly, cost reductions related to energy use can be achieved. Conventional catalyst regeneration often requires heat above 450°C for several hours and is expensive. By using temperatures between 200°C and 425°C, the energy load for catalyst regeneration is reduced, and therefore the overall production cost is lowered. Secondly, a higher rate of monoalkyl ether production by the catalyst can result in a higher yield of monoalkyl ether over the same given time interval. Conventional catalyst regeneration at best restores catalytic activity to the level of an unused catalyst. By using temperatures between 200°C and 425°C to regenerate the catalyst, greater catalytic activity can be provided to the regenerated catalyst than that exhibited by an unused catalyst. Thirdly, various heating environments (e.g., air, inert, and / or vacuum) provide process flexibility. [Examples]

[0037] material The catalyst is defined by a BEA structure, with a silica-to-alumina ratio of 25:1 and 680m 2 It is a metallosilicate catalyst with a surface area of ​​ / g, and is commercially available as CP814E from ZEOLYST INTERNATIONAL (trademark) in Conshohocken, PA.

[0038] The olefin is 1-dodecene alphaolefin, marketed as NEODENE® 12 by the SHELL® Group in The Hague, Netherlands.

[0039] Monoethylene glycol is liquid anhydrous ethylene glycol purchased from SIGMA ALDRICH®, with CAS number 107-21-1.

[0040] Test method Gas chromatography sample A gas chromatography sample is prepared by mixing a 100 μL example with a 10 mL gas chromatography solution prepared by adding 1 mL of hexadecane to 1 L of ethyl acetate. The sample is analyzed using an Agilent 7890B gas chromatography instrument. The total amount of 1-dodecene-derived species, including monoalkyl ethers, dialkyl ethers, and 2-dodecanol, 1-dodecene and all non-1-dodecenes, and other C110s. 12 Determine the total amount of dodecene, including isomers. Table 1 provides parameters for the relevant gas chromatography equipment. [Table 1]

[0041] Olefin conversion rate The olefin conversion rate is calculated by dividing the total amount of dodecene-derived species by the sum of the total amount of dodecene-derived species and the amount of dodecene. The quotient is then multiplied by 100.

[0042] Monoalkyl ether selectivity The selectivity of monoalkyl ethers is calculated by dividing the total amount of monoalkyl ethers by the total amount of dodecene-derived species. The quotient is then multiplied by 100.

[0043] Monoalkyl ether yield The yield of monoalkyl ethers is calculated by multiplying the olefin conversion rate by the monoalkyl ether selectivity.

[0044] Normalized yield The normalized yield is calculated by dividing the yield of the monoalkyl ether by the catalytic load.

[0045] Sample preparation Used air catalyst 67 g of monoethylene glycol, 62 g of olefin, and 7.5 g of catalyst are placed in a 300 mL Parr reactor equipped with a heating jacket and controller to form a reaction mixture. The reactor is sealed and heated to 150 °C while stirring at 1100 rpm using a pitch blade impeller. The mixture is allowed to react for 1 hour. The reaction mixture is removed from the reactor and the catalyst is isolated by centrifugation. This process is repeated four times to collect a sufficient amount of spent catalyst. The spent catalyst is transferred to four ceramic dishes and dried in a box oven at 110 °C with a constant airflow for 12 hours. The spent catalyst is ground into a powder using a mortar and pestle and mixed in a bottle to create a single source of dried spent catalyst.

[0046] Spent vacuum and nitrogen catalyst 67 g of monoethylene glycol, 62 g of olefin, and 7.5 g of catalyst are placed in a 300 mL Parr reactor equipped with a heating jacket and controller to form a reaction mixture. The reactor is sealed and heated to 150 °C with stirring at 1100 rpm using a pitch blade impeller. The mixture is reacted for 3.5 hours. The reaction mixture is removed from the reactor and the catalyst is isolated by centrifugation. This process is repeated four times to collect a sufficient amount of spent catalyst. The spent catalyst is transferred to four ceramic dishes and dried in a box oven at 105 °C with a constant airflow for 8 hours. The spent catalyst is ground into a powder using a mortar and pestle and mixed in a bottle to create a single source of dried spent catalyst.

[0047] Preparation of unused catalysts A portion of the unused catalyst from the supplier is placed on a ceramic dish and baked in a box oven with a constant airflow at a temperature of 550°C for 12 hours.

[0048] Air regeneration catalyst A portion of the dried, used catalyst is placed on a ceramic dish and baked in a box oven with a constant airflow at a specified temperature for a specified time.

[0049] Nitrogen regeneration catalyst A portion of the dried, used catalyst is placed on a ceramic dish and then placed in a box oven with a constant nitrogen (N2) flow for a specified time at a specified temperature.

[0050] Vacuum regenerative catalyst A portion of the dried spent catalyst is placed in a glass tube having an open end and a closed end. A vacuum pump is connected to the open end of the tube, and a heating jacket is placed around the tube. The air present in the tube is removed until a pressure of 6.65 Pa (50 μm mercury) is reached, and the sample is heated at the specified temperature for the specified time.

[0051] result The catalytic activity of the sample is tested by placing 6.2 g of 1-dodecene and 6.7 g of monoethylene glycol in a 40 mL vial reactor equipped with a rare-earth magnetic stirring rod. The magnetic stirring rod is set to stir in a tumbling style. The contents of the vial reactor are heated to a reaction temperature of 150 °C. Comparative Examples ("CE") CE1-CE4 and Examples ("IE") IE1-IE13 of the present invention are all reacted for 1 hour, while CE5-CE6 and IE14-IE16 are reacted for 1.5 hours. CE1, CE3, and CE5 are unused catalyst samples, and CE2, CE4, and CE6 are the corresponding used (i.e., unregenerated) CE1, CE3, and CE5, respectively.

[0052] Table 2 provides catalyst performance under various catalyst regeneration conditions. [Table 2]

[0053] As can be seen from the normalized yields in Table 2, the catalysts lose approximately 50% of their activity after 1–1.5 hours of reaction (i.e., used catalysts CE1, CE3, and CE5 (i.e., CE2, CE4, and CE6) produce half the yields of CE1, CE3, and CE5). The normalized yields of IE1–IE6 and IE8–IE16 surprisingly show that catalysts regenerated at 200°C–425°C provide yields equivalent to or exceeding those of unused catalysts CE1, CE3, and CE5. Also unexpectedly found are that the normalized yields of nitrogen and vacuum regenerated catalysts (IE11–IE16) are equivalent to or higher than those of unused samples (CE1, CE3, and CE5), despite the absence of oxygen for oxidizing and removing fouling (i.e., the generally accepted prior art theory). Thus, it was unexpectedly discovered that a regeneration temperature below 450°C not only provides excellent monoalkyl ether production and corresponding monoalkyl ether selectivity, but also that a non-oxygen-containing environment can also be utilized below 450°C.

Claims

1. 1. A method comprising: (a) providing a metallosilicate catalyst that has been used to catalyze a chemical reaction; (b) heating the metallosilicate catalyst to a temperature of from 200°C to 425°C for a period of from 0.5 hours to 5 hours.

2. 10. The method of claim 1, wherein the step of heating the metallosilicate catalyst is carried out in the absence of a liquid.

3. 10. The method of claim 1, further comprising catalyzing a chemical reaction of an olefin with an alcohol using the metallosilicate catalyst.

4. 4. The method of claim 3, wherein the alcohol is selected from the group consisting of methanol, ethanol, monoethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, polyethylene glycol, monopropylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,3-propanediol, 1,2-butanediol, 2,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,4-cyclohexanemethanediol, glycerol, and / or combinations thereof.

5. The olefin is 12 ~C 14 The method of claim 3 or 4, comprising an alpha-olefin.

6. 4. The method of claim 3, further comprising the step of producing a (poly)alkylene glycol monoalkyl ether.

7. 7. The method of any one of claims 1 to 6, wherein the step of heating the metallosilicate catalyst lasts for a period of 1 to 4 hours.

8. The method according to any one of claims 1 to 7, wherein the step of heating the metallosilicate catalyst is carried out at a pressure of less than 4000 Pa.

9. 8. The method of any one of claims 1 to 7, wherein the step of heating the metallosilicate catalyst is carried out under an atmosphere containing more than 99% by weight of nitrogen.

10. 10. The method of any one of claims 1 to 9, wherein the step of heating the metallosilicate catalyst is carried out at a temperature of from 250°C to 400°C.

11. 11. The method of claim 10, wherein the step of heating the metallosilicate catalyst is carried out at a temperature of from 300°C to 350°C.